ICAO’s ROLE IN ENVIRONMENTAL PROTECTION AND ITS SHORTCOMINGS UNDER RAPID GROWTH OF AVIATION INDUSTRY - Jean Claude Geofrey Mahoro (Diponegoro Law Review, 2019)
The growth of the aviation sector has significantly contributed to the global interconnectivity since World War II and presented a strong need for regulation. The Chicago Convention is the first air law that shaped the aviation industry. With that, the United Nations General Assembly set up the International Civil Aviation Organisation (ICAO) with responsibilities that could realise the aviation’s ideal. Despite this development, environmental protection was not a serious concern. However, aviation emissions and noise were later documented to be a serious threat to human health and welfare. ICAO, in its remits, has played a significant role in by establishing a regulatory framework through its policies and standards. With doctrinal method, the researcher discusses those policies and standards in the environmental perspective and their shortcomings in the prevention of GHG emissions and aircraft noise. He also reflects the importance of the United Nations Framework Convention on Climate Change (UNFCCC) 1992 and Kyoto Protocol 1997. Considerably, this paper highlights some areas that need improvements such as ICAO policies and standards’ implementation mechanisms, Global Market-Based Measure (GMBM), Radio Frequency (RF) spectrum, and conventional framework in ICAO. Hence, the researcher recommends respective stakeholders to enhance their partnership by embracing the concept of sustainability in the aviation industry.